Conceptual similarity alters the impact of context shifts on temporal memory. Issue 1 (2nd January 2021) - Gurguryan, Lauri; Dutemple, Elizabeth; Sheldon, Signy
ABSTRACT: Past work has shown that changes in encoding contexts (context shifts) act as boundaries across encountered items and can impair temporal memory. We address two questions about this effect: whether conceptual similarity among contexts creating a boundary can alleviate temporal memory impairments and if this effect holds for different forms of contexts (spatial vs. categorical). In a between-subjects design, participants studied the order of sequentially presented faces (items), each presented with an associated context. One group was shown images of a room (spatial) and the other images of a dessert (categorical) as the context. For both, boundaries between contexts with overlapping (similar) or non-overlapping (distinct) conceptual features were introduced. At test, participants performed a recency judgment for pairs of items that crossed or did not cross a context boundary at encoding and recalled whether they were encoded within the same, similar, or distinct context. For both groups, recency judgments were more accurate for item pairs from similar than distinct contexts, but memory for the context relationship between items was more accurate for items from distinct than similar contexts. Our findings suggest that conceptual knowledge impacts how events are parsed during encoding and affects temporal associations formed in episodic memory.